CENTEV/UFV Technology Incubator : Brazil Case Study - World Bank (Washington, DC, 2014)
A professor at Brazil's prestigious Federal University of Vicosa saw a need on campus for an incubator to support technologically-oriented businesses, including agribusinesses. This resulted in the CENTEV Technology Incubator, which is partially funded by the university but which also receives state and private grants. Its function is to nurture entrepreneurs to develop viable technology based businesses by providing them with management assistance and augmenting their technical capabilities with expert academic advice. The incubator s 24 graduates are still in business, with average revenues of $2.5 million a year.